Factors that influence the population's failure to access high complexity SUS services (Research, Society and Development, 2021)
Access to health is a basic human social right. The study aims to discuss the factors that influence the population's lack of access to highly complex SUS services, and to understand how health care works. This is an integrative literature review with a qualitative approach, carried out through research in electronic journals, books and legislation relevant to the subject. It is impossible to separate the vectors of human dignity and the right to health, which is an instrument of effectiveness and enforceability of rights for the exercise of constitutionalized citizenship, affirming principles of solidarity and equal rights to life, as an important ally of the community in the search for the realization of fundamental rights. The data evidenced the need for legislation that awakens the public authorities to turn their gaze and regulate in law the definition of this social problem, which is essential to break with the disrespect of the right to health. It showed that health policy control institutions play an important role in the zeal for health actions and services, through monitoring the planning, management and control instruments of the SUS and the execution of public health policies. The loss of the population from not having access to highly complex SUS services is a reality in many health units in the country, which refer to the inefficient management of human resources, and the involvement of all professionals who assist the population involved in actions is essential. Specialized qualification and frequent training.